Have school counselors assessed students’ anxiety? - Saputri, Nur Sholehah Dian; Izzaty, Rita Eka; Retnawati, Heri (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
Anxiety needs to be assessed and reduced so that it does not interfere with the mission of adolescent development. Guidance and counseling services in formal education must be provided based on the assessment of needs, one of which is in dealing with anxiety. This study was qualitative research with a type of phenomenology. The data related to the implementation of anxiety assessment were collected using interviews and observations. The participants were 15 Senior High School counselors in Yogyakarta. The data analysis was conducted using qualitative data analysis. The results of the study showed that there were still many school counselors who had not deeply assessed students’ anxiety. There were still school counselors who experienced obstacles in assessing students’ anxiety, such as regarding the time, analytical skills, students’ openness problems, and there were no instruments that could be applied easily.